Aerobic biodegradation of toluene-2, 4-di(8:2 fluorotelomer urethane) and hexamethylene-1, 6-di(8:2 fluorotelomer urethane) monomers in soils. (February 2016) - Dasu, Kavitha; Lee, Linda S.
Abstract: Aerobic soil biodegradation of toluene-2, 4-di(8:2 fluorotelomer urethane) (FTU) and hexamethylene-1, 6-di(8:2 fluorotelomer urethane) (HMU) in a forest soil and FTU in an agricultural silty clay loam soil was monitored for up to 6 months. Fluorotelomer alcohols were measured in headspace and parent monomers and all metabolites in soil extracts. Negligible degradation of FTU biodegradation occurred in the agricultural soil with 94 ± 15% recovered at day 180. However, in the forest soil, both FTU and HMU degradation was evident with significant losses of 24% (117 d) and 27% (180 day), respectively, and concomitant increases in the terminal metabolite, perfluorooctanoic acid (PFOA) concentrations were well above what could result from residual 8:2 FTOH. Kinetic modeling estimated half-lives for FTU (aromatic backbone) and HMU (aliphatic backbone) in the forest soil to be 3–5 months and 15.9-22.2 months, respectively. The addition of a structurally similar non-fluorinated FTU analog, toluene-2, 4-dicarbamic acid diethyl ester (TDAEE) enhanced production of terminal end products from 8:2 FTOH degradation. However, there was no clear evidence that TDAEE enhanced cleavage of the urethane bond, thus TDAEE appeared to just serve as an additional carbon source. TDAEE's half-life was ∼ one week. A second addition of TDAEE appeared to retard subsequent degradation of FTU exemplifying the microbial dynamics and diversity impacting degradation of polyfluoroalkyl substances. Enhanced degradation of HMU was observed upon re-aeration indicating oxygen may have been limiting during some periods although degradation of intermediate metabolites to terminal metabolites was still occurring, albeit at slower rates. Graphical abstract: Highlights: Two di-fluorotelomer (FT) urethanes aerobic biotransformation yielded perfluorooctanoic acid (PFOA). Estimated aerobic half-lives of 3–22 months for two di-FT urethane monomers. di-FT monomer with aromatic versus aliphatic backbone degraded faster. di-FT-urethane degradation was greater in forest versus agricultural soil. Addition of a non-fluorinated urethane analog did not enhance urethane cleavage.